2000
DOI: 10.1037/0894-4105.14.3.415
|View full text |Cite
|
Sign up to set email alerts
|

Visuoconstructional problems in dementia: Contribution of executive systems functions.

Abstract: Visuoconstructional ability was assessed by asking patients diagnosed with Alzheimer's disease (AD), ischaemic vascular dementia (IVD), and Parkinson's disease (PD) and a normal control group (NC) to copy a modification of the Rey-Osterrieth Complex Figure (M-ROCF). The drawings of the NC group were superior to all dementia participants. AD patients generally outperformed IVD and PD patients; however, there were few differences between IVD and PD groups. Nonetheless, the drawings of IVD and PD patients were ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
2
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 37 publications
4
51
2
3
Order By: Relevance
“…Traykov and co-workers (2002) found that AD patients had inferior performance on free and delayed recall and recognition as opposed to VaD patients, while the VaD group made more perseverative errors on the modified card sorting test, a test of executive functioning (EF). In accordance, Freeman et al (2000) observed a decrement in delayed recognition memory performance of a modification of the Rey-Osterrieth Complex Figure in AD patients compared to the VaD group, whereas the VaD group showed inferior performance on the copy condition, a condition strongly dependent upon working memory. However, differentiating these two clinical pictures based on neuropsychological tests remains indefinite (Almkvist, Fratiglioni, Aguero-Torres, Viitanen & Backman, 1999;Fahlander, Wahlin, Almkvist & Backman, 2002).…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…Traykov and co-workers (2002) found that AD patients had inferior performance on free and delayed recall and recognition as opposed to VaD patients, while the VaD group made more perseverative errors on the modified card sorting test, a test of executive functioning (EF). In accordance, Freeman et al (2000) observed a decrement in delayed recognition memory performance of a modification of the Rey-Osterrieth Complex Figure in AD patients compared to the VaD group, whereas the VaD group showed inferior performance on the copy condition, a condition strongly dependent upon working memory. However, differentiating these two clinical pictures based on neuropsychological tests remains indefinite (Almkvist, Fratiglioni, Aguero-Torres, Viitanen & Backman, 1999;Fahlander, Wahlin, Almkvist & Backman, 2002).…”
Section: Introductionsupporting
confidence: 63%
“…Tests such as the Block Design and Object Assembly test are often referred to as measuring constructional abilities (Lezak, 1995;Looi & Sachdev, 1999). However, EF such as strategy (Johanson, Gustafson & Risberg, 1986) or working memory (Freeman et al, 2000) can play an important role in constructional functions. Furthermore, a speed of processing component is present in several tasks as well, which might partly depend on EF (Desmond, 2004;Grigsby, Kaye & Robbins, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A figura complexa de Rey pode ajudar a discriminar pacientes com DA de controles [51][52][53] , mas não foram encontrados estudos brasileiros sobre este teste no diagnóstico de DA.…”
Section: Habilidades Construtivasunclassified
“…Nevertheless, a pattern emerges with consistent reports of impairments in verbal fluency, response inhibition, and mental set shifting, all characteristic of frontal systems abnormalities. Executive aspects of memory (organization and strategic encoding of information and retrieval efficiency), as well as constructional problem solving, have also been reported to be abnormal (Freeman et al, 2000).…”
mentioning
confidence: 99%